Educar em prisões: um estudo na perspectiva das representações sociais - Karol Oliveira de Amorim Silva (2016)
This research sought to analyze the process of construction of social representations of teachers who work in prisons, while education developed in this environment. The prison, historically constructed with two educational intentions - punishment and recovery - today is inserted in a movement that proposes to understand it as an educational space with a view to guarantee human rights. In this sense, it is considered that educators trained to work in other different areas of the prison, faced with the challenge of building an educational practice in this environment, anchored in ways linked to the right to education. So the main question of the research concerns the challenges experienced by educators to build knowledge and practices in the paradigm of education as a right. To do so, resorted to the use of the Theory of Social Representations of Moscovici (2012), given that interests while know this teacher, what he thinks, feels and acts like. Adopted the procedural aspect of Jodelet (2001), focusing on their movement through contributions of Antunes-Rocha (2012), with regard to the study of social representations in contexts in which subjects are induced to change their ways of thinking, feeling and acting in a new object. According to Moscovici (2012), the social representations are constructed in order to become familiar the unfamiliar, so understand that the educator in the prison context, is challenged to deal with new perspectives in the field of education, which requires him a reworking their practices and prior knowledge. This leads to the hypothesis that many of these educators take office appropriating the discussion to punish / heal, but sought with this study grasp the movements initiated by individuals to appropriate, or not, the new paradigm. To understand the prison as an inserted institution in an economic, political, social and cultural context historically built, it was adopted for this research, as reference the building society, the perspective of dialectical historical materialism (Marx and Engels 1987), contemplated the possibilities of social transformation from the concept of hegemony. In addition, to the awareness of Antonio Gramsci (1982, 2011) and education perspective for emancipation of Paulo Freire (1979, 1992, 1996, 2000). This study was part of a qualitative approach of the exploratory type, collecting data through semi-structured questionnaire (MARCONI; LAKATOS, 1996) and narrative interviews (JOVCHELOVITCH; BAUER, 2014). It is based on the proposal of thematic analysis of Bardin (1977) for processing and analysis of data. It was observed that, in addition to the discussion of the paradigm to educate the challenge of subjects in this study is the apprehension or not the difference in the specific context that affect the construction and driving their educational practices. Faced with this challenge, educators are struggling to rebuild their ways of thinking, feeling and acting education in prisons. This is achieved through two movements: permanence and change, in which they are seeking to keep the prison context in its punitive practices and anchoring their educational practices as a healing function, denying this context and looking for a "normal school" in transition, and reworking the context of the prison with a view to a contextualized education. Considers, therefore, the need to promote continue training for educators in prisons, in order to provide for them instruments that allow the construction of their practices in a critical and contextual understanding in order to provide the realization of the perspective of education.